Structural change and counter-reforms in Latin America: Necessity or possibility? - Chena, Pablo Ignacio (2020)
The issue that we present today was conceived in a very different economic, politicaland social context from the one that currently prevails due to the emergenceof a unique historical event: The Coronavirus pandemic. A phenomenon that willhave effects on economic growth and unemployment similar to those of the GreatDepression of the 1930s and an impact on human lives similar to those of a war.An economic crisis and a humanitarian crisis come together in this event.One of the central questions posed by this phenomenon is whether it will accentuatethe prevailing trends in the form of organization and articulation of productionon a world scale and global finance, or whether, by contrast, it will be a disruptivefactor and one of creative destruction. Whatever the result, the pandemic willaffect the productive structure of Latin America and the possibilities of the regionto move towards a progressive structural change.